Development of Student Worksheets Based on Science Literacy for Environmental Pollution Materials - Prilia, Sintia; Paujiah, Epa; Sholikha, Mar’atus; Mas’ud, Asrianty; Cahyanto, Tri (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to develop a Student Worksheet (LKPD) based on scientific literacy on environmental pollution material for grade X students of Senior High School. The research method employs a Research and Development (R&D) approach, utilizing a 3D model, conducted at MAN 1 in Bandung City. The instruments used include interview sheets, validation sheets, readability sheets, student response questionnaires, and student worksheets. The validation results indicate that LKPD falls into the 'valid to very valid' category, with a media expert score of 71.25% and a material expert score of 81.33%. The readability test results were 79% and 85%, respectively, and the student response was 86.4%. The average value of the limited trial reached 91. It can be concluded that LKPD, based on scientific literacy regarding environmental pollution and materials, is feasible and effective in supporting biology learning through scientific literacy. Biology teachers can apply the practical implications of this study to enhance the effectiveness of learning and serve as a reference in developing LKPD on other topics related to environmental issues.